2001
DOI: 10.1093/hmg/10.12.1287
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for BLM and Topoisomerase IIIalpha interaction in genomic stability

Abstract: The genomic instability of persons with Bloom's syndrome (BS) features particularly an increased number of sister-chromatid exchanges (SCEs). The primary cause of the genomic instability is mutation at BLM, which encodes a DNA helicase of the RecQ family. BLM interacts with Topoisomerase IIIalpha (Topo IIIalpha), and both BLM and Topo IIIalpha localize to the nuclear organelles referred to as the promyelocytic leukemia protein (PML) nuclear bodies. In this study we show, by analysis of cells that express vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
126
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 53 publications
9
126
0
Order By: Relevance
“…Instead, the double mutant induces a cellular response reminiscent of that seen following DNA damage, including focal accumulation of ␥-H2AX (Eladad et al, 2005). Despite the above discussion, Hu et al, 2001 found that the region of BLM required for PML body localization was in the N-terminal domain between residues 133 and 237 (Hu et al, 2001).…”
Section: Nonconserved N-and C-terminal Domains Of Recq Helicasesmentioning
confidence: 98%
See 1 more Smart Citation
“…Instead, the double mutant induces a cellular response reminiscent of that seen following DNA damage, including focal accumulation of ␥-H2AX (Eladad et al, 2005). Despite the above discussion, Hu et al, 2001 found that the region of BLM required for PML body localization was in the N-terminal domain between residues 133 and 237 (Hu et al, 2001).…”
Section: Nonconserved N-and C-terminal Domains Of Recq Helicasesmentioning
confidence: 98%
“…One clear role for the N-and C-terminal domains is to direct interactions with heterologous proteins. For example, BLM binds directly to topoisomerase III␣ via residues in the first 212 (likely 1-133) amino acids of the N-terminal domain, and to the RAD51 recombinase via both the N-terminal 1-212 region and the final C-terminal 150 residues (Hu et al, 2001;Johnson et al, 2000;Wu et al, 2000). Interestingly, both of these interactions and their approximate location in the RecQ helicase polypeptide are conserved between BLM and its yeast ortholog, Sgs1.…”
Section: Nonconserved N-and C-terminal Domains Of Recq Helicasesmentioning
confidence: 99%
“…When mutants are prepared that do not allow BLM localization to PML-NB, there is about a two-fold increase in sister chromatid exchange. These findings indicate that there is a need for BLM-SUMO interaction in order for BLM to localize to PML-NB, and that BLM activity, such as its accumulation at stalled replication forks, may be regulated by this specific localization [168].…”
Section: Blm: Role In Dna Damage Response With a Complex Role In Inhimentioning
confidence: 85%
“…In addition, BLM is SUMO-1 and SUMO-2 modified [167]. When mutants are prepared in which the SUMO-binding sequences are deleted, BLM cannot localize to PML-NB [168]. When mutants are prepared that do not allow BLM localization to PML-NB, there is about a two-fold increase in sister chromatid exchange.…”
Section: Blm: Role In Dna Damage Response With a Complex Role In Inhimentioning
confidence: 99%
See 1 more Smart Citation